Wakaf Uang: Implementasi di Bank Syariah Indonesia Perspektif Maslahah - Roisah, Aliyatun (Fakultas Syariah IAIN Kendari, 2024)
The research examines the implementation of cash waqf at Bank Syariah Indonesia (BSI) Kendari City Branch based on Law no. 41 of 2004 concerning Waqf, with analysis from a maslahah (benefit) perspective. The aim of this research is to assess the suitability of the implementation of cash waqf by BSI Kendari in accordance with applicable regulations and to analyze the extent to which the maslahah perspective plays a role in improving community welfare. Using qualitative research methods, this research collects data through interviews, observation and documentation of practitioners and parties directly related to cash waqf management at BSI Kendari. The research results show that BSI Kendari has not fully implemented its role as a direct cash waqf manager and still functions primarily as a facilitator, while fund management is carried out by the head office. From a maslahah perspective, this shows that there is great potential to strengthen the role of local BSI branches in direct management so that the benefits of cash waqf can be felt more optimally by the local community. Obstacles in this implementation include operational limitations at the branch level and a lack of public understanding regarding cash waqf. This research recommends steps to increase the role of branches in cash waqf management and the importance of public education about cash waqf as a productive economic instrument. By optimizing implementation according to the maslahah principle, it is hoped that cash waqf can become a significant means of economic empowerment for the community.Kata Kunci: Wakaf Uang, BSI, Maslahah